Implementation of the program "JOVIEB" in the strengthening of interpersonal values of the jóvens gives it E. A. P. UNHEVAL gives Psychology - Beraún Quiñones, Lida (2017)
The worry of realizing the present work of investigation takes root in the worry that nowadays the young persons do not have a suitable vision of the reality, to this respect there are many values that already are not practised, this owed also to that in the Educational Centers the education is more to cognitive level and it is possible to observe that they do not give him importance to the formation of the Personality, taking in counts the model of the " SOCIAL INFORMATION OF THE PERSONALITY " of the author Pedro ORTIZ CABANILLAS, it is possible to indicate to him that the levels in the development of the Personality are to Affective, Cognitive level and Conativo. Taking the model of " Interpersonal Values " of LEONARD V. GORDON bore the following indicators in mind for the present work: Support, Conformity, Recognition, Independence Benevolence and Leadership, likewise assuming that the young persons in the main are in an instability as for the strengthening of his interpersonal values, there is no a program adapted to level of Department of Education that forces the young persons to have own experiences of life in that there fortify the "Values" implanted in a certain age, to this respect, a program proposed by the Mg has been implemented. Edith Haydee Beraún Allotments, PROGRAM CALLED "JOVIEB" For the strengthening of Interpersonal Values of the Young persons, for what we have appeared the following questioning one which is the level of efficiency of the program "JOVIEB" in the strengthening of the interpersonal values of the young persons of her E. A. P. of Psychology of the UNHEVAL? Whose general aim was To implement the program "JOVIEB" Interpersonal For the strengthening of Values of the Young persons, for what we have appeared the following questioning one which is the level of efficiency of the program "JOVIEB" in the strengthening of the interpersonal values of the young persons of her E. A. P. of Psychology of the UNHEVAL? General Whose aim was To implement the program "JOVIEB" In a group of pupils of Psychology at the time there will be achieved a high level of interpersonal values in the above mentioned young persons, for the specific hypotheses, also there bore the notable indicators in mind, the same ones that were: Support, Conformity, Recognition, Independence, Benevolence and Leadership. With regard to the Type of Investigation, according to his scope it is located in an investigation quantitatively of applicative level, the design corresponds to EXPERIMETAL: Pre-experiments - Design of pre-test post-tries with an alone group. In to group of pupils of Psychology at the will swindles there be achieved to high level of interpersonal values in the above mentioned young persons, for the specific hypotheses, also there bore the notable indicators in mind, the same ones that were: Support, Conformity, Recognition, Independence, Benevolence and Leadership. With regard to the Type of Investigation, according to his scope it is located in an investigation quantitatively of applicative level, the design corresponds to EXPERIMETAL: Pre-experiments - Design of pre-test post-tries with an alone group.